An Empirical Analysis On How Conservatism Influences Cost Of Equity Capital: Evidence From Turkey - AYBARS, ASLI; EKİZLER, HÜSEYİN; ÖNER, MEHTAP (My University, 2017)
An extensive review of literature focusing on theoretical and analytical studies reveals that equity markets will benefit from accounting conservatism due to the increase in overall information quality. Conditional conservatism, which is evaluated as to the asymmetry between the impact of good and bad news on earnings, is regarded to be a substitute of discretionary disclosure. Therefore, as the firms increase the extent of their voluntary disclosures, the cost of raising capital is alleviated since this cost depends on how much information is attained by the firms’ potential investors. This study conducts a two stage analysis on a data set of nonfinancial firms listed on Borsa Istanbul 2005-2014, inclusive. Accordingly, the existence of conditional conservatism is tested by using cross-sectional regression based on the asymmetric timeliness model developed by Basu (1997) modified by Khan and Watts (2009). Consequently, the resulting firm-year measure of conditional conservatism is used as the explanatory variable of the panel data analysis. The originality of the paper stems from the fact that it attempts to provide evidence on the economic consequences of discretionary accounting practices from Turkey in this specific strand of literature related to the equity investors’ required rates of return.

Teorik ve analitik çalışmalara dayanan geniş bir literatür taraması sermaye piyasalarının, genel bilgi kalitesini arttıracağı gerekçesiyle muhasebedeki ihtiyatlılıktan fayda sağlayacağını ortaya koymuştur. İyi ve kötü haberlerin kazançlar üzerindeki asimetrik etkisi ile ölçülen koşula bağlı ihtiyatlılığın, isteğe bağlı açıklamaların yerine kullanılabildiği düşünülmektedir. Dolayısıyla, firmalar isteğe bağlı açıklamalarının miktarını arttırdıkça, sermaye bulma maliyetleri azalmaktadır; çünkü bu maliyet firmanın potansiyel yatırımcıları tarafından ne kadar bilgi edinildiğine bağlıdır. Bu çalışma, 2005- 2014 yıllarını kapsayan bir gözlem süreci boyunca Borsa İstanbul’da yer alan reel sektör firmalarına ilişkin bir veri grubu üzerinde iki aşamalı bir analiz yapmaktadır. Bu doğrultuda, koşula bağlı ihtiyatlılığın varlığı kesitsel regresyon yöntemi kullanılarak Basu (1977) tarafından geliştirilen ve sonra Khan and Watts (2009) tarafından genişletilen kazancın asimetrik zamanlılığı modeli ile test edilmiştir. Buna bağlı olarak, bahsedilen regresyon analizi sonucunda ortaya çıkan firma-yıl bazındaki koşula bağlı ihtiyatlılık ölçüsü panel veri analizinde açıklayıcı değişken olarak kullanılmıştır. Çalışmanın özgünlüğü, hisse senedi yatırımcılarının talep ettiği getiriye ilişkin bu spesifik literatür başlığında, Türkiye’deki esnek muhasebe uygulamalarının ekonomik sonuçları ile ilgili kanıt sunmaya çalışmasından ileri gelmektedir.
İhtiyatlılığın Öz Sermaye Maliyeti Üzerindeki Etkisi: Türkiye Örneği